Creating a Community of Practice Using Learning Circles: A Unique Design - Samar Ahmed; Page Morahan; Ray Wells; Diane Magrane; Paulo Carvalho; Henal Shah (Association of American Medical Colleges, 2014)
Abstract Introduction Most of our leadership development programs for faculty over the past 20 years have included learning circles (LCs), especially for programs 1 or more years in length. The LC educational group design helps participants develop conversations to link where they came from, where they are now, and where they might go. This intentional process enhances development of a deep form of community for leaders of the 21st century and goes beyond mere networking for individual gain to fostering an interrelated group that cares about the development of each individual. A key feature of the LC is a group of peers, sometimes with a senior colleague adviser. Another common feature is intentionally diverse membership. With such diversity, new solutions and friendships are possible that can fulfill the potential for dialogue, professional and personal replenishment, and wisdom-based change. Methods This resource is a complete guide to preparing and implementing LCs in an adult learning community with a multicultural flavor. Materials include a faculty guide for LCs, a syllabus for LCs (given to all faculty and program participants), large-print quotes for use in the LC, LC group composition and directions, LC agreement, and a quick-start document with step-by-step instructions. Results In 2011, 15 people participated in the session, 93% of whom percent found the session materials to be "just right," 94% strongly or very strongly agreed that they were engaged throughout the session, and 93% strongly or very strongly agreed that their knowledge and/or skills increased as a result of the session. In 2012, 14 people participated in the session, 12 of whom responded to the postsession survey. Eighty-six percent found the material in the session to be "just right," 86% strongly or very strongly agreed that they were engaged throughout the session, and 79% strongly or very strongly agreed that their knowledge and/or skills increased as a result of the session. Discussion We estimate that about a quarter of LCs stay in touch after program completion through periodic update emails, teleconferences, and Skype calls. In addition, a number of LCs have organized face-to-face meetings at conferences, each other's universities, or special weekends. Several participants have told us about adapting LCs for use in their own teaching. Our long-term goal is for all the LC participants to form a community of practice, a peer group informally bound together by personal connections and understanding, shared expertise, and passion for improving academic health centers and the people they serve. This community of practice can help drive strategy to advance our diverse health professions schools and academic health centers, solve problems of individual members, transfer effective practices, and develop individual and group professional skills.